HAMBATAN KETIDAKPATUHAN PASIEN TUBERKULOSISTERHADAP PENGOBATAN; SEBUAH STUDI KUALITATIF - Nixson Manurung (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2025)
The increasing burden of TB is caused by poverty, failure of TB activities due to inadequate political commitment and funding, unavailability of services in the community leading to reduced problem innovation and inappropriate diagnosis, reduced supply of medicines and unreported movement of people. This study aims to determine the barriers to non-adherence of tuberculosis patients to their treatment. This research is a qualitative study with a phenomenological approach. Data were collected using in-depth interviews and then analyzed using content analysis. The informants in this study consisted of 16 participants, consisting of 8 participants from the family of tuberculosis patients and 8 participants from tuberculosis patients. The results of this study found four themes, namely (1) Prolonged illness and long treatment, (2) Family persistence, (3) Interaction patterns, (4) Medication adherence. It is concluded that by knowing the obstacles of tuberculosis patients during their treatment, solutions can be found that influence increasing the patient's compliance to take medication regularly and make regular control/visits. It is also recommended that families encourage patients to continue to participate in religious activities while still complying with health procedures